Cuprous thiocyanate cross-linked porous nanosheet material as well as preparation method and application thereof
By regulating the molar ratio of copper salt and thiocyanate, the copper thiocyanate cross-linked porous nanosheet material was synthesized by ultrasonic-assisted aqueous solution liquid-phase reaction method, which solved the problems of complex preparation and low selectivity of existing Cu-based catalyst materials, and achieved efficient CO2 reduction catalysis and simplified preparation process.
Patent Information
- Application Number
- CN202311417412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
In the electrocatalytic CO2 reduction, existing Cu-based catalyst materials have problems such as complex preparation process and low single product selectivity, making it difficult to develop efficient catalysts.
By regulating the molar ratio of copper salt and thiocyanate, the copper thiocyanate cross-linked porous nanosheet material was synthesized by ultrasonic-assisted aqueous solution liquid-phase reaction method to form a cross-linked porous structure to improve catalytic activity.
This method simplifies the catalyst preparation process, improves the electrochemical activity and selectivity of the catalyst, and achieves efficient CO2 reduction catalysis. The process is environmentally friendly, with high product yields and is easy to produce on a large scale.
Smart Images

Figure CN119898798A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of inorganic catalyst materials, and in particular relates to a cuprous thiocyanate cross-linked porous nanosheet material and a preparation method and application thereof. Background Art
[0002] At present, industrial development still relies on fossil energy, resulting in high carbon emissions. To achieve the goal, the development and utilization of renewable energy (solar energy, wind energy, tidal energy, etc.) technology to reduce carbon emissions is the key. 2 ) resource utilization technologies have attracted much attention. 2 Reduction conversion technology can use renewable electricity to convert CO 2 Converting it into high-value chemicals such as CO, formic acid, and ethylene is a way to alleviate energy pressure and CO 2 After nearly a decade of research and development, electrocatalytic CO 2 Good progress has been made in catalyst development, device design, and mechanism research. 2 The central position of reduction research and the development of new and efficient catalysts remain of great significance.
[0003] Copper (Cu)-based catalyst materials not only have high electrochemical hydrogen evolution overpotential in aqueous solution, but also catalyze the conversion of CO 2 Although Cu-based materials are widely used for electrocatalytic carbon dioxide reduction, most Cu-based catalyst materials have problems such as complex preparation process and low selectivity of single product. It is necessary to develop new Cu-based catalysts for efficient electrocatalytic conversion of CO 2 There is still broad room for research. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a cuprous thiocyanate cross-linked porous nanosheet material and a preparation method and application thereof. The cross-linked porous nanosheet structure is synthesized by adjusting the molar ratio of copper salt and thiocyanate and a simple ultrasound-assisted aqueous solution liquid phase reaction method. The cross-linked porous structure is conducive to the transfer of reaction media and effectively increases the active area of catalytic reaction, thereby obtaining excellent electrochemical catalytic activity. The method has a simple production process, is environmentally friendly, has a high product yield, and is easy to scale up for production.
[0005] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:
[0006] On the one hand, the present application provides a method for preparing cuprous thiocyanate cross-linked porous nanosheet material, which has a simple production process, is environmentally friendly, has a high product yield, and is easy to scale up for production.
[0007] A method for preparing a cuprous thiocyanate cross-linked porous nanosheet material comprises the following steps:
[0008] (1) mixing an aqueous solution A containing a copper salt and an aqueous solution B containing a thiocyanate, allowing the mixture to stand, removing the supernatant, and obtaining a precipitate;
[0009] (2) centrifugally washing and drying the precipitate in sequence to obtain the cuprous thiocyanate cross-linked porous nanosheet material;
[0010] The mixing in step (1) is carried out under ultrasonic conditions;
[0011] The frequency of the ultrasound is 20 to 60 KHz;
[0012] The ultrasonic time is 20 to 50 minutes.
[0013] Optionally, the frequency of the ultrasound is independently selected from any value among 20KHz, 30KHz, 40KHz, 50KHz, 60KHz or any range therebetween.
[0014] Optionally, the ultrasound time is independently selected from any value among 20 min, 30 min, 40 min, 50 min, or any range between the two.
[0015] Optionally, the molar ratio of the copper salt to the thiocyanate in step (1) is 1:0.5-4, wherein the molar amount of the copper salt is calculated based on the molar amount of the substance itself, and the molar amount of the thiocyanate is calculated based on the molar amount of the substance itself.
[0016] Preferably, the molar ratio of the copper salt to the thiocyanate in step (1) is 1:0.5-2.
[0017] Preferably, the molar ratio of the copper salt to the thiocyanate in step (1) is 1:1.
[0018] Optionally, in step (1), the volume ratio of the aqueous solution A to the aqueous solution B is 1.5-4:1-3.
[0019] Preferably, in step (1), the volume ratio of the aqueous solution A to the aqueous solution B is 3:2.
[0020] Optionally, the copper salt in step (1) includes at least one of copper nitrate, copper chloride, copper acetate and copper sulfate.
[0021] Optionally, the thiocyanate in step (1) includes at least one of potassium thiocyanate, sodium thiocyanate and ammonium thiocyanate.
[0022] Optionally, the standing time in step (1) is 0.5 to 2 hours.
[0023] Optionally, the standing time in step (1) is independently selected from any value among 0.5h, 1h, 1.5h, 2h, or any range between the two.
[0024] Optionally, the centrifugal washing in step (2) is performed by sequentially using water and ethanol.
[0025] Optionally, the rotation speed of the centrifugal washing in step (2) is 7000-8000 r / min;
[0026] The number of centrifugal washing in step (2) is ≥ 2 times;
[0027] The time for each centrifugal washing in step (2) is 2 to 4 minutes.
[0028] Preferably, the number of centrifugal washing in step (2) is 3 times.
[0029] Optionally, the drying in step (2) is vacuum drying.
[0030] Optionally, the vacuum drying temperature is 50-70°C;
[0031] The vacuum drying time is 5 to 7 hours.
[0032] In a second aspect, the present application provides a cuprous thiocyanate cross-linked porous nanosheet material prepared by the above preparation method. The cuprous thiocyanate cross-linked porous nanosheet material is conducive to the transfer of reaction media and effectively increases the active area of catalytic reaction, thereby obtaining excellent electrochemical catalytic activity.
[0033] In a third aspect, the present application provides the use of the above-mentioned cuprous thiocyanate cross-linked porous nanosheet material as a catalyst material.
[0034] In a fourth aspect, the present application provides the use of the above-mentioned cuprous thiocyanate cross-linked porous nanosheet material in electrocatalytic carbon dioxide reduction.
[0035] Compared with the prior art, this application has the following beneficial effects:
[0036] (1) The preparation method of cuprous thiocyanate (CuSCN) cross-linked porous nanosheet material provided in the present application is simple, environmentally friendly, has a high product yield, and is easy to scale up for production.
[0037] (2) The cuprous thiocyanate (CuSCN) cross-linked porous nanosheet material provided in the present application is used as an electrochemical carbon dioxide reduction catalyst, exhibiting excellent catalytic activity and selectivity, thus enriching the types of electrochemical carbon dioxide reduction catalysts.
[0038] (3) The CuSCN cross-linked porous nanosheet structure material provided in this application has potential application value in photocatalysis and dye-sensitized solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 This is the X-ray diffraction pattern of the CuSCN cross-linked porous nanosheet material prepared in Example 1 of the present application;
[0041] Figure 2 Field emission scanning electron micrograph of the CuSCN cross-linked porous nanosheet material prepared in Example 1 of the present application (Note: (a) represents an electron micrograph of CuSCN (scale is 10 μm); (b) represents a further enlarged electron micrograph of CuSCN (scale is 1 μm));
[0042] Figure 3 The Faraday efficiency curve of the product of the CuSCN cross-linked porous nanosheet material prepared in Example 1 of the present application for electrocatalytic carbon dioxide reduction at different potentials (relative to the reversible hydrogen electrode);
[0043] Figure 4 Field emission scanning electron micrograph of the CuSCN (CuSCN-1#) material prepared in comparative example 1 of the present application under non-ultrasonic conditions (Note: (a) represents the electron micrograph of CuSCN-1# (scale is 3 μm); (b) represents the electron micrograph of CuSCN-1# further enlarged (scale is 1 μm));
[0044] Figure 5 Field emission scanning electron micrograph of the CuSCN (CuSCN-2#) material prepared in comparative example 2 of the present application (Note: (a) represents the electron micrograph of CuSCN-2# (scale is 1 μm); (b) represents the further enlarged electron micrograph of CuSCN-2# (scale is 300 nm)). DETAILED DESCRIPTION
[0045] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0046] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0047] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0048] The instruments used in the following examples are: an ultrasonic cleaning machine (KQ-400DE model), a field emission scanning electron microscope (Hitachi SU-8020 model), and an electrochemical workstation (CHI760, Shanghai Chenhua).
[0049] Example 1
[0050] Preparation of CuSCN cross-linked porous nanosheet materials:
[0051] (1) Weigh 1 mmol of copper acetate dihydrate and dissolve it in 30 mL of deionized water, labeled as solution A;
[0052] (2) Weigh 1 mmol of potassium thiocyanate and dissolve it in 20 mL of deionized water, labeled as solution B;
[0053] (3) Add liquid B to liquid A at an ultrasonic frequency of 40 kHz and perform ultrasonic reaction for 30 min;
[0054] (4) taking out and letting it stand at room temperature for 1 h, removing the supernatant and obtaining the precipitate;
[0055] (5) The precipitate was washed with deionized water and anhydrous ethanol at 7500 r / min for 3 times (3 min each time), and then vacuum dried at 60° C. for 6 h to obtain the CuSCN cross-linked porous nanosheet material.
[0056] Example 2
[0057] Characterization of material samples:
[0058] The phase and morphology of the CuSCN sample prepared in Example 1 were detected by X-ray powder diffractometer and scanning electron microscope. The test results are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2It can be seen that X-ray powder diffraction shows that the prepared CuSCN is pure phase ( Figure 1 ), scanning electron microscopy shows that the CuSCN sample is a cross-linked porous nanosheet structure ( Figure 2 ).
[0059] Example 3
[0060] Preparation of CuSCN coated on carbon paper (CuSCN / CC) electrode:
[0061] The CuSCN material prepared in Example 1 was used as a carbon dioxide reduction catalyst and loaded on carbon paper. The sample loading on the electrode surface was 1 mg / cm 2 The electrode prepared is CuSCN / CC. The specific steps are as follows: 5 mg of the synthesized sample is dispersed in 1000 μL of a mixed solution of water, ethanol, isopropanol and perfluorosulfonic acid (nafion) (volume ratio is water: ethanol: isopropanol: nafion = 9:6:3:2) and ultrasonically dispersed to form a suspension. The suspension is dropped on a carbon cloth (the area of the carbon paper is 1×1.5 cm 2 ) to make the sample loading on the carbon paper electrode 1.0 mg / cm 2 After natural drying, an electrode sheet for catalytic carbon dioxide reduction is obtained, which is recorded as CuSCN / CC.
[0062] Example 4
[0063] Electrochemical test of CuSCN / CC electrode:
[0064] The catalytic activity and selectivity of the electrode CuSCN / CC prepared in Example 3 were tested. 2 Saturated 0.1M KHCO 3 , testing the carbon dioxide reduction reaction (abbreviated as CO 2 RR) to test the distribution of catalytic carbon dioxide reduction products at different potentials.
[0065] The results are as follows Figure 3 As shown, the electrode CuSCN / CC exhibits good electrocatalytic carbon dioxide reduction performance. Within the tested voltage range, it can achieve a peak Faradaic efficiency of 80% for the generation of one-carbon products (formic acid and CO), which proves the excellent selectivity of the electrode CuSCN / CC for catalytic carbon dioxide reduction.
[0066] Comparative Example 1
[0067] Preparation of CuSCN-1# material:
[0068] (1) Weigh 1 mmol of copper acetate dihydrate and dissolve it in 30 mL of deionized water, labeled as solution A;
[0069] (2) Weigh 5 mmol of potassium thiocyanate and dissolve it in 20 mL of deionized water, labeled as solution B;
[0070] (3) At room temperature, add liquid B to liquid A and stir evenly;
[0071] (4) Allow the reaction to stand for 1 h, remove the supernatant and obtain the precipitate;
[0072] (5) The precipitate was washed with deionized water and anhydrous ethanol at 7500 r / min for 3 times (3 min each time), and then vacuum dried at 60° C. for 6 h to obtain the CuSCN-1# material.
[0073] The phase and morphology of the CuSCN-1# sample prepared in Comparative Example 1 were detected by scanning electron microscopy. The detection results are as follows: Figure 4 The results show that the comparative sample CuSCN-#1 has an irregular structure similar to the antler morphology.
[0074] Comparative Example 2
[0075] Preparation of CuSCN-2# material:
[0076] (1) Weigh 1 mmol of copper acetate dihydrate and dissolve it in 30 mL of deionized water, labeled as solution A;
[0077] (2) Weigh 5 mmol of potassium thiocyanate and dissolve it in 20 mL of deionized water, labeled as solution B;
[0078] (3) Add liquid B to liquid A at an ultrasonic frequency of 40 kHz and perform ultrasonic reaction for 30 min;
[0079] (4) taking out and letting it stand at room temperature for 1 h, removing the supernatant and obtaining the precipitate;
[0080] (5) The precipitate was washed with deionized water and anhydrous ethanol at 7500 r / min for 3 times (3 min each time), and then vacuum dried at 60° C. for 6 h to obtain the CuSCN-2# material.
[0081] The phase and morphology of the CuSCN-2# sample prepared in Comparative Example 2 were detected by scanning electron microscopy. The detection results are as follows: Figure 5 The results show that the CuSCN-#2 sample is a stacked irregular nanosheet structure.
[0082] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a cuprous thiocyanate cross-linked porous nanosheet material, characterized in that: The steps include: (1) mixing an aqueous solution A containing a copper salt and an aqueous solution B containing a thiocyanate, allowing the mixture to stand, removing the supernatant, and obtaining a precipitate; (2) centrifugally washing and drying the precipitate in sequence to obtain the cuprous thiocyanate cross-linked porous nanosheet material; The mixing in step (1) is carried out under ultrasonic conditions; The frequency of the ultrasound is 20 to 60 KHz; The ultrasonic time is 20 to 50 minutes.
2. The method for preparing the cuprous thiocyanate cross-linked porous nanosheet material according to claim 1, characterized in that: The molar ratio of the copper salt to the thiocyanate in step (1) is 1:0.5-4, wherein the molar amount of the copper salt is based on the molar amount of the substance itself, and the molar amount of the thiocyanate is based on the molar amount of the substance itself.
3. The method for preparing the cuprous thiocyanate cross-linked porous nanosheet material according to claim 1, characterized in that: In step (1), the volume ratio of the aqueous solution A to the aqueous solution B is 1.5-4:1-3.
4. The method for preparing cuprous thiocyanate cross-linked porous nanosheet material according to claim 1, characterized in that: The copper salt in step (1) includes at least one of copper nitrate, copper chloride, copper acetate and copper sulfate; Preferably, the thiocyanate in step (1) includes at least one of potassium thiocyanate, sodium thiocyanate and ammonium thiocyanate.
5. The method for preparing the cuprous thiocyanate cross-linked porous nanosheet material according to claim 1, characterized in that: The standing time in step (1) is 0.5 to 2 hours.
6. The method for preparing cuprous thiocyanate cross-linked porous nanosheet material according to claim 1, characterized in that: The centrifugal washing in step (2) is performed by centrifugation using water and ethanol in sequence; Preferably, the rotation speed of the centrifugal washing in step (2) is 7000-8000 r / min; The number of centrifugal washing in step (2) is ≥ 2 times; The time for each centrifugal washing in step (2) is 2 to 4 minutes.
7. The method for preparing cuprous thiocyanate cross-linked porous nanosheet material according to claim 1, characterized in that: The drying in step (2) is vacuum drying; Preferably, the vacuum drying temperature is 50-70°C; The vacuum drying time is 5 to 7 hours.
8. The cuprous thiocyanate cross-linked porous nanosheet material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the cuprous thiocyanate cross-linked porous nanosheet material according to claim 8 as a catalyst material.
10. Use of the cuprous thiocyanate cross-linked porous nanosheet material according to claim 8 in electrocatalytic carbon dioxide reduction.